FORMULATION AND OPTIMIZATION OF PIOGLITAZONE SOLID DISPERSIONS PREPARED BY HOT MELT EXTRUSION TECHNIQUE - Vidyadhara Suryadevara; Ashis Kumar Mehatha; Sasidhar R Lankapalli; Abhijit M Deshmukh; Laxmana P Sambath (Indonesian Journal of Pharmacy, 2013)
The main objective of the present study was to develop a novel and stable pioglitazone loaded solid dispersions with enhanced solubility and dissolution rate. Different drug-to-carrier ratios were prepared by employing hot melt extrusion technique. These formulations were characterized for solid state properties by differential scanning calorimetry, X-ray powder diffraction and FT-IR spectral studies. Formulations were further evaluated for dissolution and stability studies. The aqueous solubility of pioglitazone, in present formulation was improved by the presence of both the polymers. Solid-state characterization indicated pioglitazone was present as amorphous material in formulation with Soluplus and polyethylene glycol, due to efficient entrapment in polymer matrix. The diffraction patterns of solid dispersion indicated the amorphous nature of pioglitazone in solid dispersions. The dissolution rate of all the solid dispersions was found to be rapid when compared to pure pioglitazone. Pioglitazone in pure form has very slow dissolution rate, when compared with the solid dispersions. Thus the solid dispersion prepared with Soluplus and polyethylene glycol would be useful for delivering poorly soluble pioglitazone with enhanced solubility and dissolution rate.Key words: pioglitazone, soluplus, solid dispersions, melt extrusion technique.